Оптимізація доставки замовлень з автоматично підібраних закладів громадського харчування - Перетятко, М. В. (ХНУРЕ, 2019)
The object of research is the catering industry, namely the process of finding nutrition based on the individual characteristics of a particular user with the ability to order dishes. The goal of the work is to develop a system that stores information about the eating habits and preferences of clients, the goals of the daily calorie diet, nutrition styles, lists of banned and authorized products, and based on user profiles, it selects the food establishments with the possibility of ordering food and delivery. orders in intelligent smart boxes that support the set temperature and determine their geographical location, which is transmitted on the map.